Some properties of fuzzy path connected Topological spaces - Sukainh Mahmod Ali Almabrok , Almbrok Hussin Alsonosi Omar (Journal of Pure & Applied Sciences, 2019)
The aim of this paper is to study the some properties of fuzzy path connectedness in fuzzy topological spaces. Different way will be provided to prove that fuzzy path connected space is fuzzy connected by using the concept of fuzzy connected component and also to prove that the Cartesian product of two fuzzy path connected spaces is also fuzzy path connected.